Study of the sexual and reproductive health of young women with visual impairment - Joshi, Prajakta Ganesh; Joshi, Ganesh Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Census figures in 2011 have depicted that half of the visually impaired in India are women and a third of these females are in reproductive age group. This study was undertaken to identify the gynaecological health problems of the visually impaired young women and impart them necessary health education. Methods: All young visually impaired women attending composite regional centre for persons with disabilities, Bhopal during one day were offered consultation by gynecologist. Their needs and clinical findings were recorded. Results: There were 15 young women in the age range of 19 to 27 years participating in the study. This was their first ever visit to gynecologist. More than half of them reported that menstrual hygiene was taught to them by their mother, a third by peers, and one participant each reported that sister, aunt, and teacher helped them learn it. The cramping pain and warmth of discharge per vaginum helped them identify the onset of menses. Primary dysmenorrhea was the commonest complaint for which they relied on rest and over the counter available medicine. Conclusions: This study highlights the need of the inclusion of the visually impaired girls in adolescent reproductive and sexual health education with appropriate teaching learning material. Access to a gynecologist for the visually impaired shall be ensured through camps on regular basis and referral on individual need basis.